The impact of inflation targeting: Testing the good luck hypothesis - Federico Ravenna (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
Over the last twenty years the level and volatility of inflation decreased across industrial countries. The inflation behaviour can be explained by a shift in monetary policy or by a lucky period of low volatility in business cycle shocks. To test theluck hypothesis we examine the inflation experience of Canada, one of the earliest and most successful adopter of an inflation targeting monetary policy. We Kalman-filter the historical structural shocks consistent with an estimated DSGE model, but allow for part of the variance in the data to be explained by a vector of non-structural random innovations. The estimated DSGE model shocks are used to build counterfactual histories. Ex-ante the estimated model predicts inflation volatility to more than halve under inflation targeting. But conditional on the shocks, we show that the luck hypothesis can explain with a high probability Canada's low inflation volatility since the early 1990s. Any inflation stabilization induced by the shift in policy is accounted for the most part by the impact on expectations. Counterfactuals built neglecting expectations would prove the inflation targeting policy irrelevant.
Keywords: E42; E52; E58; 330; business cycle shocks; Kalman filter; credibility; inflation targeting; Inflation Targeting; Inflationsbekämpfung; Ökonometrisches Makromodell; Schätzung; Kanada